Evaluation the Antibacterial Effects of Two Commercial Products of Eucalyptus globulus Against Common Microbial Causes of Respiratory Tract Infections - Mohammadreza Nahaei, Mahsa Kalejahi 1, Parisa Rahbarfam 1, Solmaz Maleki Dizaj 2, Farzaneh Lotfipour * (Tabriz University of Medical Sciences, 2016)
Background: Recently, antimicrobial activity of medicinal plants have attained once more importance due to drug resistance of microbial isolates to common antibiotics as well as fewer side effects and low cost of herbal products comparing to chemical drugs. Eucalyptus globules (E. globulus) has been widely applied as a natural remedy in respiratory tract infections. The present study focused on the evaluation of antibacterial effect of two commercial products of E. globulus against common microbial causes of respiratory tract infections. To this end, two commercial products of E. globules including inhaler and oral soft capsule with standard expiration date, (in three different batch numbers) were purchased from the pharmacy stores of Tabriz city. Methods: The antibacterial efficiency of these products were investigated using Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and disk diffusion methods against Staphylococcus aureus, Streptococcus pyogenes and Pseudomona aeruginosa. Results: Based on the obtained results, these commercial products of E. globules showed significant inhibitory effects against Gram-positive bacteria. The findings also indicated that the Eucalyptus inhaler products had more inhibitory effects than Eucalyptus oral soft capsule, however batch to batch variations were of concern. Conclusion: This research presents optimistic result on using the Eucalyptus as an alternative antibacterial agent against respiratory tract pathogenic microorganisms.